A comparison between non-monotonic formalisms - Delladio, Telma (2006)
It is interesting and important to compare, analyze and assess the alternative tools that could be used in the area of Knowledge Representation. In this paper we present a reasearch line associated to this goal: to formally establish the relation among Knowledge Representation formalisms in order to make a sensible use of them. As a part of this main task, we present a comparison between Normal Default Theory and Defeasible Logic Programming. This comparison is achieved introducing a DELP variant, called DELP;, which allows to associate the answers of a DELP interpreter to the consequences, credulous and skeptical, of a Normal Default Theory.